Analisa Sistem Penerangan Lampu Jalan Di Desa Kenten Laut Banyuasin - Wendy Juniar Akbar; Emidiana Emidiana; Yudi Irwansi (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2023)
In evaluating street lighting systems, the main factors are safety, comfort, and beauty for road users who must receive special attention. Street lighting is very useful at night or during dark conditions such as rain or cloudiness. Therefore, the authors evaluate the street lamp lighting system on the street .A.Nakowi .No17.Rt14 in the village of KentenLaut. From the results obtained, the length of the road is 240 meters with a road width of 4 meters for the calculation of the installation of street lights based on the reality in the field by taking into account road conditions and road classification. The lamp used is SON-T 150W, after an evaluation, the street lamp lighting system on the street. A.Nakowi.No17..Rt14.In the village of KentenLaut does not meet the standards, so the street lamps in the village of KentenLaut must be repaired or replaced with lamps so that the lighting can match the standard of street lamp lighting, the standard of good street lamp lighting is 20 lux so that road users feel comfortable with bright lighting.